Controlling joint instability delays the degeneration of articular cartilage in a rat model. Issue 2 (February 2017) - Murata, K.; Kanemura, N.; Kokubun, T.; Fujino, T.; Morishita, Y.; Onitsuka, K.; Fujiwara, S.; Nakajima, A.; Shimizu, D.; Takayanagi, K.
Summary: Objective: Joint instability induced by anterior cruciate ligament (ACL) transection is commonly considered as a predisposing factor for osteoarthritis (OA) of the knee; however, the influence of re-stabilization on the protection of articular cartilage is unclear. The aim of this study was to evaluate the effect of joint re-stabilization on articular cartilage using an instability and re-stabilization ACL transection model. Design: To induce different models of joint instability, our laboratory created a controlled abnormal joint movement (CAJM) group and an anterior cruciate ligament transection group (ACL-T). Seventy-five Wistar male rats were randomly assigned to the CAJM ( n  = 30), ACL-T ( n  = 30), or no treatment (INTACT) group ( n  = 15). Cartilage changes were assessed with soft X-ray analysis, histological and immunohistochemistry analysis, and real-time polymerase chain reaction (PCR) analysis at 2, 4, and 12 weeks. Results: Joint instability, as indicated by the difference in anterior displacement between the CAJM and ACL-T groups ( P  < 0.001), and cartilage degeneration, as evaluated according to the Osteoarthritis Research Society International (OARSI) score, were significantly higher in the ACL-T group than the CAJM group at 12 weeks ( P  < 0.001). Moreover, joint re-stabilization maintained cartilage structure (thickness [ P  < 0.001], surface roughness [ P  < 0.001], and glycosaminoglycan stainability [ P  < 0.001]) and suppressed tumor necrosis factor-alpha (TNF-α) and caspase-3 at 4 weeks after surgery. Conclusion: Re-stabilization of joint instability may suppress inflammatory cytokines, thereby delaying the progression of OA. Joint instability is a substantial contributor to cartilage degeneration.